(untitled) (CAHIERS MAGELLANES-NS, 2024)
Reading ability is the basic component to get an eduction particularly for students with hearing impairment. It plays an important part in the development of linguistic, academic and social skills of individuals from their school year onwards. This study aims to assess the written expression abilities of hearing-impaired students who receive auditory-oral instruction and look into the factors influencing student performance through a multimodal approach. The subjects taken for this study include 10 third and fourth graders from Kerala's Royal School for Hearing Impaired. The multimodal intervention included tools such as fingerspelling, sign language, table writing, air writing, and the "see and say" method. A computer programme designated "Statistical Package for the Social Sciences" (SPSS) Version 20.0 was used to methodically investigate the results of both the immediate and delayed post-tests. The independent samples t-test was used to compare the experimental and control groups for the immediate and delayed post-tests for parametric samples. Key findings indicate significant improvements in students' abilities to learn the alphabet, numerals, and sight words, with post-test scores showing marked increases from pre-test levels. The multimodal approach not only enhanced reading fluency but also improved students' engagement and retention of learning material. These results are important as they demonstrate that integrating multiple sensory modalities can effectively address the unique learning needs of hearing-impaired students, thereby supporting their academic development and inclusion in mainstream education.